'L'homme nouveau': L'humanisme de Jean Sénac face à la 'tragédie algérienne'. (1st February 2013) - Combe, Dominique
The trauma of the Algerian War and of decolonization in the 1950s and 1960s triggered a new awareness in France, which, building on the thought of Camus, Sartre and M. Merleau-Ponty emerging from the experience of World War II and the division between East and West, contributed to a questioning of humanist thought. The work of the French poet Jean Sénac, who was born and lived in Algeria after independence, and who was assassinated in 1973, bears witness to this profound crisis in humanism in a decisive moment in history, philosophy and poetry. The poems published by Camus from 1954 onwards, together with the unpublished tragedy Le Soleil interdit, written between 1954 and 1958, represent the collapse of the humanist dream to reconcile 'citizens of beauty' into an Algeria united by fraternity.